GGT and GSH-triggered nanoplatform for efficient gambogic acid delivery and tumor penetration in triple-negative breast cancer - Su Li; Qinghua Wang; Chen Su; Zhen Jia; Guoshuang Shen; Mengting Da; Rui Yang; Jiuda Zhao; Daozhen Chen (Materials Today Bio)
Emerging nanodrug delivery strategies seek to overcome tumor heterogeneity and enhance drug penetration in the dense matrix of solid tumors. This study presents a dual-responsive nanoplatform, poly(lactic-co-glycolic acid)-disulfide-polyethylene glycol-glutamate (PLGA-SS-PEG-Glu) loaded with Gambogic acid (GA), engineered to exploit γ-glutamyltranspeptidase (GGT) and glutathione (GSH) triggers specific to the triple-negative breast cancer (TNBC) microenvironment. Designed with Boc-L-Glutamic Acid-1-tert-butyl ester (Boc-Glu-OtBu), this nanoplatform achieves enzyme-triggered charge reversal to enhance tumor penetration, facilitating GGT-induced charge-switching and GSH-responsive GA release. In vitro, PLGA-SS-PEG-Glu@GA shows potent cytotoxicity (IC50 = 0.80 μg/ml) against 4T1 TNBC cells, inducing apoptosis and inhibiting cell proliferation through energy-dependent, GGT-mediated endocytosis. Compensatory Nrf2/HO-1 activation mechanistically induced by GA-loaded nanoplatform ultimately potentiated mitochondrial apoptotic pathway (Bcl-2/caspase-3) initiation, promoting apoptosis. In vivo, this nanoplatform leveraged its tumor-specific enzymatic and redox microenvironment-responsive properties to achieve enhanced deep intratumoral penetration. Treatment for 2 weeks effectively suppressed primary tumor growth, while extended therapy to one month significantly inhibited the formation of pulmonary metastatic foci. This dual-responsive strategy not only elevates drug bioavailability at the tumor site but also provides a promising solution to overcome critical barriers in solid tumor drug delivery.